Multiwaveband analysis of brightest GRB070125 - Chandra, P.; Cenko, S.; Frail, D.; Chevalier, R.; Macquart, Jean-Pierre; Kulkarni, S.; Bock, D.; Bertoldi, F. (2008)
We present a comprehensive multiwavelength analysis of the bright, long duration gamma-ray burst GRB 070125, comprised of observations in ?-ray, X-ray, optical, millimeter and centimeter wavebands. Radio light curves show rapid flux variations, which are interpreted as due to interstellar scintillation, and are used to derive an upper limit of 2.4×10 17cm on the radius of the fireball. Radio light curves and spectra suggest that the afterglow shock wave is moving in a dense medium. Our broadband modeling favors a constant density profile for the circumburst medium over a wind-like profile (R-2). GRB 070125 is a burst with high radiative efficiency (>60%). © 2008 American Institute of Physics.